International practices in forensic speaker comparisons: second survey. (5th June 2019) - Gold, Erica; French, Peter
Abstract : A survey relating to current practices in forensic speaker comparison testing was recently undertaken of 39 laboratories and individual practitioners across 23 countries. Questions were organised around a number of themes, including the preliminary assessment and preparation of case materials, the checking of analysts' work, frameworks used for the expression of conclusions, the use of automatic speaker recognition systems, the use of reference populations, and awareness of cognitive bias. Developmental trends in this area of forensic speech science are established by comparing responses to the present survey with those to the authors' earlier survey published in 2011.